IMPROVING USE RESTRICTION WITH MODIFIED ATTRIBUTES- BASED ALGORITHMS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article considers the issues of improving the process of restricting access in automated information systems of commercial banks. In order to eliminate the shortcomings of the traditional role-based access control (RBAC) method, which are associated with lack of flexibility and non-accountability of attributes, a modified algorithm is proposed, integrated with the attribute-based access control (ABAC) approach. The proposed method allows determining access rights based on user roles and attributes, as well as resource attributes. The article develops a two-stage algorithm for granting access rights and verifying access in information systems of commercial banks. This approach serves to increase the security of bank information resources, reduce unauthorized access, and optimize the process of authority management.